Organizational culture and social equity an experiential guide - Dolamore, Stephanie; Kline, Angela (New York Routledge, 2023)
"Social equity, or the lack of social equity, is practiced in all of our organizations. By focusing on advancing an equitable organizational culture, public and nonprofit organizations can improve internal operations, retain skilled public servants, and fundamentally fulfil their mission to serve the community. Social equity is often explored as a grand theory, but it is critical for organizations to identify and practice strategies to apply theory into action. Organizational Culture and Social Equity: An Experiential Guide is the first book of its kind to provide the public service-minded reader with an opportunity to practice social equity. The chapters are designed to be both theoretical and practical, helping the reader develop knowledge to analyze social equity efforts in their own organization as well as the tools to act. The contributing chapter authors in this book explore social equity through various dimensions of organizational culture: physical characteristics and general environment; policies, procedures, and structures; socialization; leadership behavior; rewards and recognition; discourse; and learning and performance. Each contributor provides a thorough overview of their respective culture category along with important theories and concepts, definitions, and strategies for practice. The chapter authors then examine social equity in each area of organizational culture through a learning activity, discussion questions, and a 'Call to Action.' Each chapter further reinforces concepts with a vignette featuring a public administrator who has faced a situation related to that chapter. Organizational Culture and Social Equity is a timely and essential read for all those who wish to study or practice public administration through an equity lens"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Corporate culture; Employee motivation; Leadership; Personnel management